CO₂-갈탄 가스화 반응에 미치는 폐촉매의 영향 및 반응속도론 연구 - 서석진(Seok-Jin Seo); 이소정(So-Jung Lee); 손정민(Jung Min Sohn) (Clean Technology, 20(1), 2014)
본 연구에서는 갈탄에 폐촉매(I, II, III) 및 K2CO3를 이용한 CO2 가스화의 반응속도상수 및 활성화 에너지를 조사하였다. 가스화 실험은 1 wt%, 5 wt%, 10 wt%의 촉매를 물리적으로 혼합한 갈탄을 열중량분석(Thermogravity analysis, TGA)을 이용하여 가스화 온도 800 ℃, 850 ℃, 900 ℃ 범위에서 수행하였다. 실험 데이터를 세 가지 반응속도 모델(volumetric reaction model,VRM; shrinking core model, SCM; modified volumetric reaction model, MVRM)에 적용한 결과 MVRM이 가장 적합하였다. 가스화 속도는 온도가 높아짐에 따라 증가하는 것으로 관찰되었으며, 모든 실험 온도에서 폐촉매를 이용한 가스화 반응의활성화 에너지는 촉매를 혼합하지 않은 갈탄 보다 낮게 나타났다. 특히, 폐촉매 III 10 wt%의 경우 활성화 에너지가 92.37kJ/mol로 가장 낮게 얻어졌다. In this study, we investigated reaction rate constant and activation energy of CO2 lignite gasification by using wastecatalysts (I, II, III) and K2CO3. The gasification experiments were conducted with the lignite which was mixed physically with thecatalysts of 1 wt%, 5 wt%, 10 wt% by thermogravimetry with TGA at 800 ℃, 850 ℃ and 900 ℃. The experimental data wasanalyzed with kinetic models (VRM, SCM and MVRM). MVRM was the most suitable among the three models. It wasconfirmed that gasification rate increased with increasing temperature and the activation energies of CO2 gasification of lignitewith mixed waste catalysts were lower than that of lignite alone at all temperatures. Especially, 10 wt% of waste catalyst IIIshowed the lowest activation energy, 92.37 kJ/mol, among all lignite-char with catalysts. KCI Citation Count: 4